Failure-mode-hierarchy-based design for reinforced còncrete structures - Neocleous, Kyriacos; Pilakoutas, Kypros; Guadagnini, Maurizio (My University, 2005)
Innovations in concrete construction can be held back by the inability of codes of practice to accommodate new materials. The current design and safety philosophy (DSP) of reinforced concrete relies heavily on the properties of steel reinforcement. The need to embrace new materials, such as fibre-reinforced polymer (FRP) reinforcement, led to an in-depth examination of the DSP of European concrete codes of practice and resulted in a new philosophy, presented in this paper. The basis of the new philosophy remains the limit-state design and achievement of target notional structural reliability levels, but aims at the attainment of a desired failure mode hierarchy. The implementation of the philosophy, through a proposed framework, utilises the concept of average measure of closeness for the determination of appropriate material partial safety factors. An example of the application of the proposed framework is presented for FRP reinforcement. © 2005 Thomas Telford and fib.
Keywords: Fiber reinforced plastics; Concrete beams and girders; Beams reinforced